Research on the city image and cognitive distance based on chromatogram at the scale of mega city in Wuhan - Shouni Tang; Hongbo Qiao; Huizhen Yang; Wei Liu; Xixi Huo; Guoqing He; Bin Ma (Journal of Asian Architecture and Building Engineering, 2023)
The research studies the city image and cognitive distance at the scale of mega city scale in Wuhan. In the research, lots of people’s attitudes data towards city images were collected by questionnaire in 15 areas and analyzed by mathematical software. Moreover, they are presented by chromatogram. The following conclusions are drawn. The research obtains a lot of data on people's attitude data through the investigation and finds that the city images of Wuhan have changed with the expansion of the city. Also, the research finds that chromatogram is feasible to analyze the city image. As for the attitude data of people, the research analyzed it with distance data. Hankou beach, Hubu Lane, Wuhan Yangtze River Bridge, Yellow Crane Tower and Wuhan University show significant correlation according to the results. The nearest metro stations around these five images are generally above 1 km. However, for the correlation analysis of Jianghan Road Walkway, Guiyuan Buddhist Temple, Optical Valley Business District, East Lake Scenic Area of Wuhan and Han Street, the results show that there is no correlation. The nearest metro stations around these five images are generally less than 1 km.